Distribution of sasX, mupA, and qacA/B genes and determination of genetic relatedness of epidemic methicillin-resistant Staphylococcus aureus strains associated with bloodstream infections in southern China - Zhao, Rui; Du, Bingyu; Hu, Lingling; Li, Chenxi; Xue, Fen; Wang, Xing; Jiang, Changhong; Wang, Jinghua; Zhao, Yanfeng (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMethicillin-resistant Staphylococcus aureus (MRSA) exhibits diverse genotypes with varying virulence and resistance profiles, particularly in the context of bloodstream infections (BSI). This study investigates the prevalence of the sasX, mupA, and qacA/B genes among MRSA isolates from bloodstream infections in southern China and analyzes their genetic relatedness.MethodsA polymerase chain reaction (PCR) assay was developed to detect the presence of the sasX gene, which is associated with nasal colonization, immune evasion, and virulence, the mupirocin resistance gene mupA, and the chlorhexidine tolerance gene qacA/B in a total of 77 MRSA isolates. Multilocus sequence typing (MLST) was performed to determine the sequence types (STs) and assess the genetic relatedness of the isolates. The resistance of these strains to 16 antibiotics was also analyzed. The distribution of these genes and their association with epidemic STs were analyzed.ResultsA total of 26 STs were identified, with notable prevalence in five epidemic clones: ST59, ST5, and ST764. The prevalence of the sasX, mupA, and qacA/B genes across all isolates was 23.4%, 33.8%, and 79.2%, respectively. Specifically, the frequency of the sasX gene was highest in ST59 (29.4%), ST239 (100%), and ST764 (37.5%); mupA was most prevalent in ST5 (66.7%), ST59 (17.6%), ST764 (37.5%), and ST15 (100%); qacA/B was predominantly found in ST59 (88.2%), ST5 (66.7%), ST398 (85.7%), ST764 (50.0%), and ST239 (100%). The gene distribution patterns revealed that sasX+ qacA/B+ mupA+ strains were closely associated with epidemic clones ST6290 and ST88, whereas sasX+ qacA/B+ mupA- strains were linked to ST59, ST239, and ST764. DiscussionNotably, forty-seven (61%) MRSA BSI strains were multidrug-resistant, with the majority exhibiting resistance to penicillin, erythromycin, and clindamycin. Major MRSA clones in southern China include ST59, ST5, ST764, and ST398. In this study, sasX, mupA and qacA/B genes were present in the MRSA isolates, with the mupA gene being the most prevalent. Variations in the prevalence of virulence and resistance genes among these epidemic strains underscore the need for targeted infection control measures. These findings contribute to a better understanding of the genetic epidemiology of MRSA in the region, facilitating the development of effective prevention and control strategies for BSI.